Hubungan Dukungan Suami, Aktivitas Fisik, Dan Stress Pada Ibu Hamil Trimester 1 Terhadap Kejadian Hyperemesis Gravidarum Di TPMB Yunita : The Relationship Between Husband's Support, Physical Activity, and Stress in Pregnant Women in the First Trimester and the Incidence of Hyperemesis Gravidarum at TPMB Yunita - Yunita (Indonesian Scholar Journal of Nursing and Midwifery Science, 2024)
Introduction: Hyperemesis gravidarum is excessive nausea and vomiting so that daily work is disrupted and the general condition becomes worse. Nausea and vomiting are the most common disorders encountered in the first trimester of pregnancy, around 60-80% of primigravidas and 40-60% of multigravidas experience nausea and vomiting but these symptoms become more severe only in 1 out of 1,000 pregnancies. Husband's support, physical activity, and stress influence the incidence of hyperemesis gravdiarum. This study aimed to determine the relationship between husband's support, physical activity, and stress in first-trimester pregnant women to the incidence of hyperemesis gravidarum at TPMB Yunita in 2023. Methods: The research method used an analytic descriptive design with a cross-sectional approach. The sampling technique was total sampling with 30 first-trimester pregnant women. Results: The results showed that there was a relationship between the husband's support (p-value 0,005); physical activity (p-value 0,001); and stress (p-value 0.002) to the incidence of hyperemesis gravidarum. Discussion: The study concludes a relationship between husband's support, physical activity, and stress in trimester I pregnant women to the incidence of hyperemesis gravidarum at TPMB Yunita in 2023. Suggestions for pregnant women are expected to be able to manage the physical activity carried out to be of higher quality and not too excessive during pregnancy by limiting activities that are too strenuous such as doing housework continuously and lifting heavy weights.